AGREEMENT AND DISAGREMENT FUNCTION IN DISCOURSE MARKER WELL IN DEBATE NIGHT AMERICA PROGRAM: A PRAGMATICANALYSIS - Veronika Listi Ferdini Damopolii (LLDIKTI Wilayah X, 2021)
The research entitled “Discourse Marker Well in Debate Night in America Interview Program.” The objectives of this research are to analyze and describe two types and two functions of discourse marker well which occur in Debate Night in America Program. This marker that frequently occurs in the program demonstrates a special sort of discourse marker well in particular news interviews. This study uses description method to analyze the research. Pragmatic is used to approach the analysis, which is mainly developed by Schiffrin (1987). He called discourse markers as linguistics expressions, which can be a word or phrase. The results of this study show ten discourse markers well that frequently occur in Debate Night in America Program. In term of functions, the frequently marker proposes various functions. The marker serves its own function in guiding the hearer and the audience to interpret the intended meaning of the speaker. In addition, the functions of discourse marker well provide particular purpose by the speaker in order to influence and attract the voters. The function analyzed in the use of discourse marker well is to show agreement and disagreement.